A rapid, non‐destructive method for sampling castrating parasites in endangered bivalve molluscs. Issue 3 (4th December 2020) - Brian, Joshua I.; Aldridge, David C.
Abstract: Bivalves are important ecosystem engineers, and there is emerging evidence that many species are afflicted with castrating parasites. Understanding the prevalence of these largely overlooked parasites is crucial in understanding the fundamental biology of bivalves, informing conservation efforts, and providing a wider understanding of host–parasite dynamics. Current techniques to assess the presence of parasites are destructive, making them untenable for endangered or protected populations. This article presents a non‐destructive method of sampling bivalve molluscs ( Anodonta anatina ) to detect castrating trematodes. Gonadal fluid is removed with a hypodermic needle from bivalves in situ and analysed in a laboratory setting without removing the mollusc from the field; this sampling mechanism has previously been shown not to harm the mollusc. A single 50 μl sample is sufficient to detect both the presence and developmental stage of the trematode with greater than 95% reliability, with all but the lightest infections visible. We recommend that this technique should be used to enhance knowledge on host–parasite dynamics in bivalves, and inform sensible conservation for threatened species.